2012
DOI: 10.1016/j.coph.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant pharmacological therapies for COPD

Abstract: Increased oxidative stress occurs in the lungs and systemically in COPD, which plays a role in many of the pathogenic mechanisms in COPD. Hence, targeting local lung and systemic oxidative stress with agents that modulate the antioxidants/redox system or boost endogenous antioxidants would be a useful therapeutic approach in COPD. Thiol antioxidants (N-acetyl-L-cysteine and N-acystelyn, carbocysteine, erdosteine, and fudosteine have been used to increase lung thiol content. Modulation of cigarette smoke induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 93 publications
1
73
0
3
Order By: Relevance
“…COPD patients treated with carbocysteine experienced fewer numbers of exacerbations per year (Zheng et al 2008). This effect may be linked to the reduced adherence of bacterial pathogens to airway epithelial cells (Rahman and Macnee 2012) and to the downregulation of ICAM-1, a receptor for the major group of rhinovirus (Yasuda et al 2006). Moreover, carbocysteine inhibiting cell apoptosis and promoting the reversal of the imbalance of proteolytic and anti-proteolytic enzyme activities protects against the development of CSEinduced emphysema in rats (Hanaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD patients treated with carbocysteine experienced fewer numbers of exacerbations per year (Zheng et al 2008). This effect may be linked to the reduced adherence of bacterial pathogens to airway epithelial cells (Rahman and Macnee 2012) and to the downregulation of ICAM-1, a receptor for the major group of rhinovirus (Yasuda et al 2006). Moreover, carbocysteine inhibiting cell apoptosis and promoting the reversal of the imbalance of proteolytic and anti-proteolytic enzyme activities protects against the development of CSEinduced emphysema in rats (Hanaoka et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of carbocysteine seems to be more related to its antioxidant and anti-inflammatory effects than to its mucolytic activity (Rahman and Macnee 2012). Limited information is available on the comparative effects between carbocysteine and a potent corticosteroid, fluticasone, in cellular models with elevated oxidative stress due to cigarette smoke exposure.…”
Section: Introductionmentioning
confidence: 99%
“…NAC, an acetyl derivative of the amino acid cysteine, neutralizes ROS by reducing disulfide bonds. NAC may also enhance intracellular levels of glutathione in vivo in several organs, including the lungs (649). Importantly, investigations conducted in healthy subjects have shown that treatment with NAC delays fatigue and increases glutathione availability in response to chronic endurance training (650,651).…”
Section: Antioxidantsmentioning
confidence: 99%
“…Thus, there is great interest in the use of antioxidants to prevent and treat smoking-related lung disease. Thiol compounds such as N-acetylcysteine and carbocysteine have been extensively studied, as well as mimetics of superoxide dismutase and glutathione peroxidase, and inhibitors of nitric oxide synthase (4,49).…”
Section: L168 Inhibitors Of Acute Cigarette Smoke-induced Inflammationmentioning
confidence: 99%